Média ponderada : interpretação geométrica e relações com outras médias - Azevedo, Alikson Nascimento de (2023)
In this work, we will present a geometric interpretation of the means: Arithmetic, Geometric, Harmonic, Quadratic and the harmonic root mean square of two positive numbers and a generalization of these means in the circle. Next we consider a geometric interpretation of the Weighted Average and its relationship to the other averages. We will also present an analysis made by Pappus of Alexandria on the geometric construction of means: Arithmetic, Geometric and Harmonic. Next, we studies an mean generating function and a geometric interpretation of the Weighted mean on the trapezoid and in a rectangle. Finally, we present some practical applications of the mean in the last chapter and a complementary result in the appendix.